1991
DOI: 10.1007/bf00186257
|View full text |Cite
|
Sign up to set email alerts
|

Optical diffraction by well-ordered muscle fibres

Abstract: We have studied the diffraction of a focussed laser beam by single fibres of glycerinated rabbit psoas muscle as a function of the angle of incidence. Diffraction efficiencies as high as 34% were observed at the first-order Bragg angle, indicative of well-ordered striated fibres with a strong periodic modulation of the refractive index. A theory is presented to account for our observations based upon the coupled-wave model developed by Kogelnik (1967) and Magnusson and Gaylord (1977) for the description of thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
29
0

Year Published

1993
1993
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(33 citation statements)
references
References 27 publications
4
29
0
Order By: Relevance
“…7), by using a three dimensional coupled wave theory [5,25]. A physical sarcomere structure model and properties proposed by Thornhill et al [5,26] was used in the calculation. The sarcomere length used was 2.8 μm.…”
Section: Resultsmentioning
confidence: 99%
“…7), by using a three dimensional coupled wave theory [5,25]. A physical sarcomere structure model and properties proposed by Thornhill et al [5,26] was used in the calculation. The sarcomere length used was 2.8 μm.…”
Section: Resultsmentioning
confidence: 99%
“…In order to test this, we applied a three dimensional coupled wave theory [27] in a semi-infinite Monte Carlo model. The sarcomere structure model and properties proposed by Thornhill et al [28] was used in the calculation. Each sarcomere was taken as a single grating with following geometrical parameters: sarcomere length = 3.1μm, length of A band =1.5μm, and length of I band = 2.0μm.…”
Section: Discussionmentioning
confidence: 99%
“…Each sarcomere was taken as a single grating with following geometrical parameters: sarcomere length = 3.1μm, length of A band =1.5μm, and length of I band = 2.0μm. A photon packet experienced regular scattering events as in the conventional Monte Carlo model [28] with Henyey-Greenstein phase function. However, in between two consecutive scatterings, the photon had a probability to be diffracted instead of following a ballistic trajectory.…”
Section: Discussionmentioning
confidence: 99%
“…However, his model was not capable of analyzing muscle fibers with different striation patterns. On the basis of the work of Huxley and Hanson's work [11] on refractive index modulation in sarcomeres, Thornhill et al [12] described a much improved sarcomere model and applied the first-order coupled wave theory developed by Kogelnik [13]. Sidick et al [14] further introduced rigorous coupled wave analysis for planar diffraction (2DCW) [15] to analyze light diffraction in muscle fibers for TE polarization.…”
Section: Introductionmentioning
confidence: 99%
“…We hypothesized that such apparent inconsistencies can be explained if the inhomogeneous nature of the muscle fibers was taken into consideration. Most of the previous theoretical studies assumed that muscle fiber had a uniform and wellorganized myofibril arrangement featuring straight, skewed, or sinusoidal ripple striations [7,12,[17][18][19]. On the other hand, microscopic studies have shown that morphological and optical parameters do not remain constant throughout a myofibril [20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%